A feasible method for measuring the buildability of fresh 3D printing mortar. (10th December 2019) - Yuan, Qiang; Li, Zemin; Zhou, Dajun; Huang, Tingjie; Huang, Hai; Jiao, Dengwu; Shi, Caijun
Highlights: Buildability of 3D printing mortar was evaluated by the deformation of stacking layers. A deformation monitoring device was designed to monitor the deformation of printing layer. An equation between the optimal interval time and structural build-up rate was proposed. Abstract: The buildability of fresh concrete is of great importance to 3D printing technology. In this paper, the buildability of 3D printing mortar was evaluated from the perspective of deformation of fresh mortar during the process of printing. A deformation monitoring device was designed to monitor the change of deformation of printing layer with stacking. The physical and chemical effects on the evolution of structural build-up were evaluated by the growth rate of static yield stress and penetration resistance. Results showed that the chemical effect was more effective than the physical effect, and the combination of physical and chemical effects was the most effective one. The growth of penetration resistance had a linear relationship with the growth of static yield stress, and both of them can be used to characterize the structural build-up of fresh mortar. The deformation value and optimal printing interval time could be obtained by simulating the printing process using the deformation monitoring device. An equation between the optimal interval time and the growth rate of static yield stress was established.